Trans fatty acids increase nitric oxide levels and pancreatic beta-cell necrosis in rats - Kusmiyati Tjahjono DK; Santoso Santoso; Dwi Ngestiningsih (Universa Medicina, 2013)
BACKGROUND The prevalence of diabetes in Indonesia is increasing due to various factors, including life style changes such as trans fatty acid (TFA) intake. High TFA intake is known to be related to blood lipid profile changes resulting in cardiovascular disorders. This study was to identify the effect of TFA on nitric oxide (NO) production and on necrosis of pancreatic beta cells. METHODS A study of randomized pre-test post–test design with control group. Thirty Sprague Dawley rats were divided into 3 groups, i.e. group K (control), group P1 receiving a diet with 5% TFA, and P2 receiving 10% TFA. The intervention was performed for 8 weeks. NO level and pancreatic beta-cell necrosis were analyzed using Pearson’s chi square test. RESULTS After 4 weeks of treatment there was no change in NO levels in group K, but increased NO in P2 (2.6-3.8 ìM). At 8 weeks after treatment, NO levels in groups P1 and P2 increased to 2.6-3.4 ìM and 4.2-14.3 ìM, respectively, while in group K only 2 rats had increased NO levels of 2.8-2.9 ìM. With Pearson’s chi-square test, there was a signifant difference in the proportions of necrotic pancreatic beta cells after 4 weeks and 8 weeks (p= 0.000). No necrosis of beta cells was found in group K, mild necrosis in group P1 (1-25%) and moderate necrosis in group P2 (26-50%). CONCLUSION TFA consumption significantly increases NO levels in Sprague Dawley rats and also results in moderate grades of necrosis of pancreatic beta cells